Exchange Rate Volatility and Leading Export Commodities of Plantations in Indonesia: The Gravity Model Approach - Fahma Muslima; Bayu Kharisma (Jurnal Economia, 2023)
AbstractThe plantation sector is a sector that has an important and strategic role in development. This is reflected in the role of the plantation sector as a provider of employment opportunities, meeting the domestic industry's needs for consumption and raw materials and achieving added value through increased competitiveness. This study aims to analyze the effect of the real exchange rate and volatility on Indonesia's leading plantation export commodities to trade partner countries from 1997 to 2016. The research method used is the estimated gravity model with fixed or random effects. The results showed that the exchange rate and volatility positively and negatively affected plantation exports. Thus, the Government must adopt policies to increase the competitiveness of domestic products and anticipate competition between domestic exporters. In addition, exchange rate stabilization policies are needed to control volatility to reduce uncertainty's impact on Indonesia's plantation exports.Keywords: Exchange Rate, Leading Estate Crops, Export, Panel Data, Gravity Model